Modelling the atypical absorption of menatetrenone and the metabolism to its epoxide: effect of VKORC1 polymorphism. - Baek, I. H.; Kang, W.; Yun, H. Y.; Lee, S. S.; Kwon, K. I. (Journal of Clinical Pharmacy & Therapeutics, 2011)
This study aimed to model the atypical absorption of menatetrenone and its epoxide metabolite and to examine the influence of the single nucleotide polymorphism (SNP) of vitamin K2 epoxide reductase complex subunit 1 (VKORC1) on the pharmacokinetics. After the administration of 30 mg of menatetrenone to 26 healthy subjects, the plasma concentrations of menatetrenone and its epoxide were measured using LC-MS/MS. For the haplotype analysis, the SNP of the VKORC1 gene was investigated in the 26 volunteers. The model parameters were estimated using the ADAPT II program. A two-compartment model with Weibull-type absorption and saturable elimination described the pharmacokinetics of menatetrenone and its epoxide. The plasma concentrations of both tended to be lower in the H1/H7 genotype group than in the wild-type H1/H1 group. We present the first detailed pharmacokinetic modelling of menatetrenone in relation to VKORC1 genotype. This study suggests that VKORC1 genotype is unlikely to be helpful in dose-selection because of the very high inter-individual variation in systemic exposure within each genotype group, and the small inter-group difference observed.